Documenta 8 : Führer durch die Ausstellung - Metken, Günter (Kassel : Verlag Documenta GmbH, 1987)
Allen, Terry ; Applebroog, Ida ; Armajani, Siah ; Armleder, John ; Artschwager, Richard ; Aycock, Alice ; Baquié, Richard ; Beuys, Joseph ; Boltanski, Christian ; Bosslet, Eberhard ; Bruch, Klaus vom ; Brummack, Heinrich ; Burton, Scott ; Bustamante, Jean-Marc ; Cage, John ; Carr-Harris, Ian ; Collyer, Robin ; Cragg, Tony (Anthony) ; Dossi, Ugo ; Ecker, Bogomir ; Endo ; Fischl, Eric ; Friedmann, Gloria ; García Sevilla, Ferran ; Gerz, Jochen ; Goldstein, Zvi ; Golub, Leon ; Görlich, Ulrich ; Gormley, Antony ; Grosvenor, Robert ; Günther, Ingo ; Haacke, Hans ; Finlay, Ian Hamilton ; Harrison, Newton ; Hien, Albert ; Holzer, Jenny ; Huber, Stephan ; Huene, Stephan von ; Jaar, Alfredo ; Jetelova, Magdalena ; Julius ; Karavan, Dani ; Kawamata, Tadashi ; Kemps, Niek ; Kiefer, Anselm ; Klauke, Jürgen ; Klein, Astrid ; Knoebel, Imi ; Komar & Melamid ; Kruger, Barbara ; Kumrow, Klaus ; Lafontaine, Marie-Jo ; Laib, Wolfgang ; Lang, Nikolaus ; Lavier, Bertrand ; Leccia, Ange ; Levine, Les ; Longo, Robert ; Luy, Wolfgang ; Magor, Liz ; Maier-Harrison, Helen ; Material, Group ; Merz, Gerhard ; Metzel, Olav ; Morris, Robert ; Nechvatal, Joseph ; Nestler, Wolfgang ; Nordman, Maria ; Odenbach, Marcel ; Opie, Julian ; Oppermann, Anna ; Penone, Giuseppe ; Plessi, Fabrizio ; Prinz, Bernhard ; Rabinowitch, David ; Radermacher, Norbert ; Richter, Gerhard ; Rosenbach, Ulrike ; Rückriem, Ulrich ; Sarmento, Julião ; Scholte, Rob ; Schütte, Thomas ; Serra, Richard ; Solano, Susana ; Spitzer, Sergej ; Tansey, Mark ; Tevet, Nahum ; Trakas, George ; Ullman, Micha ; Vercruysse, Jan ; Vieille, Jacques ; Virnich, Thomas ; Wakolbinger, Manfred ; Wall, Jeff ; Walther, Franz Erhard ; Wewerka, Stefan ; Witlatschil, Michael ; Wodiczko, Krzysztof ; Wolf, Silvio ; Wonder, Erich ; Woodrow, Bill
Documenta 8, Kassel, 12 juni tot 20 september 1987
Duits
boek